Anthropometric and physical characteristics allow differentiation of young female volleyball players according to playing position and level of expertise - Milic, M.; Grgantov, Z.; Chamari, K.; Ardigò, L. P.; Bianco, A.; Padulo, J. (Biology of Sport, 2017)
The aim of our study was to determine the differences in some anthropometric and physical performance variables of young Croatian female volleyball players (aged 13 to 15) in relation to playing position (i.e., independent variable) and performance level within each position (i.e., independent variable). Players were categorized according to playing position (i.e., role) as middle blockers (n=28), opposite hitters (n=41), passer-hitters (n=54), setters (n=30), and liberos (n=28). Within each position, players were divided into a more successful group and a less successful group according to team ranking in the latest regional championship and player quality within the team. Height and body mass, somatotype by the Heath-Carter method, and four tests of lower body power, speed, agility and upper body power (i.e., dependent variables) were assessed. Players in different positions differed significantly in height and all three somatotype components, but no significant differences were found in body mass, body mass index or measured physical performance variables. Players of different performance level differed significantly in both anthropometric and physical performance variables. Generally, middle blockers were taller, more ectomorphic, less mesomorphic and endomorphic, whereas liberos were shorter, less ectomorphic, more mesomorphic and endomorphic than players in other positions. More successful players in all positions had a lower body mass index, were less mesomorphic and endomorphic, and more ectomorphic than less successful players. Furthermore, more successful players showed better lower body power, speed, agility and upper body power. The results of this study can potentially provide coaches with useful indications about the use of somatotype selection and physical performance assessment for talent identification and development.